(untitled) (Sport and Tourism Central European Journal, 2022)
In theoretical studies on the typology of tourists, various criteria for their identification can be found. A drawback of this approach is the lack of one common concept of tourist division, which would allow for comparing research results at various academic and marketing centers. There is a definition problem of tourism and the tourist themselves, the concepts often differing from each other, thus, there is no common ground on which the theories of the separation and division of tourists can be built. In the presented publication, a review of selected, varying tourist types have been conducted. Typologies of tourists are based on various criteria, ranging from sociological and psychological to demographic, geographic, economic, marketing and others often having an inter- disciplinary basis. First of all, attempts were made to show the diversity of typological concepts presented in the world. They are used in scientific research but only refer to a small group of respondents and it is difficult to compare the results with other results based on other divisions. In conclusion, a new, proprietary division has been proposed, which, it seems, could be used by various academic centers, allowing greater possibilities for the comparison of research results in the area of tourism. It is based on the awareness and subjective understanding of the phenomenon of tourism which is interpreted differently in many areas and environments.